Towards improvingthe effectiveness of the public procurement rules of Bangladesh:lessons from the United Nations procurement manual - Uddin, Mohammed Salah (BRAC University, 2018)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2018.